Konseling Kelompok Behavioral Berbasis Modeling Simbolik: Upaya Peningkatan Tanggung Jawab Akademik Mahasiswa - Latifah, Leny; Yasni Sanaky, Nur; Soejanto, Laily Tiarani (Universitas PGRI Kanjuruhan Malang, 2025)
Academic responsibility is an important attitude that students must have in order to achieve academic success. However, there are still students who do not fully understand the importance of responsibility in fulfilling their academic obligations. This study aims to determine the effectiveness of behavioral group counseling based on symbolic modeling in efforts to increase students' academic responsibility. The study used a one-group pretest-posttest design with a quantitative approach. The subjects in this study were 12 students from PGRI Kanjuruhan University in Malang who were selected using purposive sampling. The instruments used were an academic responsibility scale, and the data were analyzed using the Wilcoxon test with the assistance of SPSS 22. The results of the analysis showed a significant increase in academic responsibility scores after the treatment was administered (p < 0.05). Thus, behavioral group counseling based on symbolic modeling is effective in improving students' academic responsibility